A FINANCIAL RISK MANAGEMENT POLICY FOR NON-FINANCIAL CORPORATIONS - Finn, Sean; Laroche, Pierre; Vallée, Luc (Assurances, 2000)
Given that there exist many reasons why a firm should hedge its exposure to financial risks, this paper proposes a financial risk management policy for non-financial corporations. These corporations are mostly end-users of derivatives securities for hedging purposes, whereas financial institutions are also issuers and intermediaries. This is why we adapted generally accepted financial risk management principles, since they were originally designed for financial institutions. Our policy is derived from the one recently adopted by a large Canadian firm and its compliance to G30 recommendations has been acknowledged by international consultant firm. A rating agency also mentioned that the policy constitutes a positive element in a report issued a few months after it has been implemented.